Radical Decarboxylative Carbometalation of Benzoic Acids: A Solution to Aromatic Decarboxylative Fluorination - Xu, Peng; López-Rojas, Priscila; Ritter, Tobias (Journal of the American Chemical Society, 2021)
Abundant aromatic carboxylic acids exist in great structural diversity from nature and synthesis. To date, the synthetically valuable decarboxylative functionalization of benzoic acids is realized mainly by transition-metal-catalyzed decarboxylative cross couplings. However, the high activation barrier for thermal decarboxylative carbometalation that often requires 140 °C reaction temperature limits both the substrate scope as well as the scope of suitable reactions that can sustain such conditions. Numerous reactions, for example, decarboxylative fluorination that is well developed for aliphatic carboxylic acids, are out of reach for the aromatic counterparts with current reaction chemistry. Here, we report a conceptually different approach through a low-barrier photoinduced ligand to metal charge transfer (LMCT)-enabled radical decarboxylative carbometalation strategy, which generates a putative high-valent arylcopper(III) complex, from which versatile facile reductive eliminations can occur. We demonstrate the suitability of our new approach to address previously unrealized general decarboxylative fluorination of benzoic acids.